2020
DOI: 10.1186/s12871-020-00978-z
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine is an effective sedative agent for electroencephalography in children

Abstract: Background: Intranasal dexmedetomidine (DEX), as a novel sedation method, has been used in many clinical examinations of infants and children. However, the safety and efficacy of this method for electroencephalography (EEG) in children is limited. In this study, we performed a large-scale clinical case analysis of patients who received this sedation method. The purpose of this study was to evaluate the safety and efficacy of intranasal DEX for sedation in children during EEG. Methods: This was a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
3
5
2
1
Order By: Relevance
“…It has been reported to be non-noxious to the nasal mucosa in different studies [24,25]. But in the present study, nasal discomfort was observed in 2 children with IND administration, which could be due to administration of the drug by a syringe and would have been best avoided with the use of a mucosal atomizer device [28], whereas a success rate of 87% was reported in a similar study using IND at a dose of 2.5 µg/kg [29]. In a recent systematic review, the success rate of IND was shown to vary from 30 to 100% depending on the dose of the drug and type of procedures requiring sedation [10].…”
Section: Discussioncontrasting
confidence: 63%
“…It has been reported to be non-noxious to the nasal mucosa in different studies [24,25]. But in the present study, nasal discomfort was observed in 2 children with IND administration, which could be due to administration of the drug by a syringe and would have been best avoided with the use of a mucosal atomizer device [28], whereas a success rate of 87% was reported in a similar study using IND at a dose of 2.5 µg/kg [29]. In a recent systematic review, the success rate of IND was shown to vary from 30 to 100% depending on the dose of the drug and type of procedures requiring sedation [10].…”
Section: Discussioncontrasting
confidence: 63%
“…Contrastingly, most cats had deep sedation in the IM group 5-10 min after drug administration. Notably, IN administration of anesthetic drugs has variable peak sedation times in different species [6,12]. The onset of IN dexmedetomidine in humans has been reported at 45 min after administration [14,15], whereas 6.3 ± 3.3 min in dogs [6].…”
Section: Discussionmentioning
confidence: 99%
“…This represents a convenient, simple, and noninvasive administration approach [8,10]. Recently, IN dexmedetomidine has been applied in children [5,[11][12][13]. The drug delivery effectiveness through the IN route that targets the brain has been previously shown in humans [14,15] and dogs [6,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Tiene la gran ventaja de no desencadenar apnea, ni incrementar la secreción salival; su repercusión en el calibre de las vías aéreas es mínima; 10,11 mayor con propofol, midazolam y halogenados. 12,13,14 La dosis sugerida es de 1.5 -2 mcg por kg de peso intravenoso, a pasar lentamente, siempre con monitoreo continuo, tipo I como mínimo, y aporte de oxígeno. Es importante recordar que no es recomendable la administración en bolo intravenoso.…”
Section: S78 S79unclassified